Flexible perovskite light-emitting diodes: recent progress, applications and challenges - Ying Li; Tingyi Gao; Ziquan He; Chenxi Shen; Siqian Zhou; Mingze Li; Daquan Zhang; Qianpeng Zhang; Yu Fu; Xiaoliang Mo; Zhaoyu Zhang; Wengang Bi; et al. (npj Flexible Electronics)
Abstract Significant progress has been made in perovskite light-emitting diodes (PeLEDs) over the past decade, with external quantum efficiencies (EQEs) exceeding 30% for green and red emissions, and 20% for blue emissions. However, the performance and device area of flexible PeLEDs remains constrained due to issues such as crack formation and short circuits that occur during device deformation. These challenges limit their applicability in flexible, stretchable, and wearable displays and lighting solutions. This review systematically summarizes recent advancements in flexible PeLEDs, focusing on various strategies to improve their flexibility and performance. We first discuss the use of flexible substrates and electrodes in these devices. Next, we examine the fabrication methods and the mechanical and optoelectronic properties of different perovskite materials used in flexible PeLEDs, including three-dimensional (3D) thin films, low-dimensional nanomaterials, and perovskite/polymer composites. Finally, we highlight the extensive applications of flexible PeLEDs in wearable optoelectronics and provide an outlook on the future development of high-performance flexible PeLEDs to facilitate their commercialization.